Biomechanical performance of retrograde nail for supracondylar fractures stabilization. - Chantarapanich, Nattapon; Sitthiseripratip, Kriskrai; Mahaisavariya, Banchong; Siribodhi, Pongwit (Medical & Biological Engineering & Computing, 2016)
The study compared the biomechanical performance of retrograde nail used to stabilize supracondylar fracture (three different levels) by means of finite element analysis. Three different nail lengths (200, 260, and 300 mm) of stainless steel and titanium nails were under consideration. Intact femur model was reconstructed from Digital Imaging and Communications in Medicine images of Thai cadaveric femur scanned by computed tomography spiral scanner, whereas geometry of retrograde nail was reconstructed with the data obtained from three-dimensional laser scanner. The retrograde nail was virtually attached to the femur before nodes and elements were generated for finite element model. The finite element models were analyzed in two stages, the early stage of fracture healing and the stage after fracture healing. The finding indicated that purchasing proximal locking screw in the bowing region of the femur may be at risk due to the high stresses at the implant and bone. There were no differences in stress level, elastic strain at a fracture gap, and bone stress between stainless steel and titanium implant. Since the intramedullary canal requires reaming to accommodate the retrograde nail, the length of retrograde nail should be as long as necessary. However, in case that the retrograde nail can be accommodated into the intramedullary canal without reaming, the longer retrograde nail can be used.